Les coalitions dans l’analyse des politiques urbaines post-keynésiennes - Rémi Dormois (Métropoles)
In this article, we study the formation of coalitions in urban regeneration projects implemented in Genova (Italy), Sheffield (Great Britain) and Saint-Etienne (France). The results discussed in this article are based on a research funded by the French Ministery for the Sustainable Development2.The first part deals with a review of recent literature concerning the role of coalitions in the urban policies. We underline the benefit – for theory and methodology issues – that can be retired by the use of the Urban Regime Theory in the analysis of coalitions.In a second part we compare our results and existing works about the composition and the role of coalitions in urban policies. We show that coalitions existing in urban regeneration policies are less cross-sectoral – with the weakness of social actors – than coalitions studied in American and English cities. We underline also that existing several coalitions in parallel acting in different types of urban renewal areas (social housing settlement, mixed neighborhood with high potentiality of valorization).In the last part, we insist on the role attempted of urban regeneration projects to structure a local collective action capacity. These projects are not set up only to respond at economic and social issues but also to find a solution at the governmentability crisis of cities with the fragmentation of decision arenas. But this objective is partially achieved because inhabitants and other social actors don’t take part directly at the design of this projects.